Experimental Gastric Non-Balloon Devices - Youn I Choi; Kyoung Oh Kim (Korean Society of Gastrointestinal Endoscopy, 2018)
Endoscopic bariatric therapies (EBTs) are promising alternatives to the conventional surgeries used to treat obesity and related metabolic conditions, targeting gastrointestinal anatomical and physiological processes. Many EBTs are at various stages of development and are aimed at promoting an early sense of satiety via anatomical and physiological mechanisms. In the present study, we focused on relevant clinical issues and future perspectives with regard to gastric non-balloon methods treating obesity.